Liver resection in monolobar Caroli’s disease - Mollard, Lourdes; Gasque, Rodrigo A.; Chahdi Beltrame, Magali; Lenz, Marcelo E.; Mattera, Francisco J.; Quiñonez, Emilio G. (Revista Argentina de Cirugía, 2026)
Caroli’s disease is a congenital disorder caused by a defect of the ductal plate. The clinical picture includes intrahepatic duct lithiasis and recurrent cholangitis usually in young people. The imaging tests reveal the presence of multifocal and segmental dilatation of the intrahepatic bile ducts. Cholangiocarcinoma can develop as a long-term complication of chronic bile duct inflammation and should always be considered as a differential diagnosis. We describe a rare case of a 52-year-old woman who presented with bile duct obstruction after laparoscopic cholecystectomy and required resection of liver segments II and III due to Caroli’s disease with a favorable outcome